II-08 Complement receptors 1 and 2 on B cell subsets are negatively associated with lupus disease activity. (August 2018) - Rosenthal, Shoshana; Reinhold, Dominik; Jones, Kenneth L; Zhang, Weiming; Pearson, Duane; Lough, Kara M; Boackle, Susan A
Abstract : Background: B cell complement receptor 1 (CR1) and complement receptor 2 (CR2) levels are decreased by ∼50% in subjects with systemic lupus erythematosus (SLE). CR2 but not CR1 levels have been negatively correlated with lupus disease activity. However, increased CR1 expression on B cells is associated with a protective polymorphism in the CR2 gene. We conducted a longitudinal analysis of B cell CR1 and CR2 to further evaluate an association with lupus disease activity and to determine whether it is driven by specific cell subsets. Methods: Thirty-six subjects meeting the revised 1982 ACR criteria for SLE were enrolled. Each subject had a baseline visit and 1 to 4 follow up visits, with additional visits for flares. Peripheral blood mononuclear cells (PBMC) were stained with a dead cell marker and antibodies to CD19, CD27, and IgD. Antibody binding capacity (ABC) of CR1 and CR2 on live bulk and gated B cells was determined using quantitative flow cytometry (Bang Labs). The frequency of live gated B cells was determined. Disease activity was measured using SLEDAI. Statistical analyses were performed using R. To determine associations between the SLEDAI scores and gate/quadrant signals, negative binomial mixed effect models were fitted using the glmmADMB package. A random effect intercept was included to account for different individual baseline SLEDAI scores. The gate/quadrant signals, in terms of ABC and percentages, were the independent variables. Adjustments were made for age, prednisone dose, and, where relevant, bead lot. To account for multiple testing in bulk B cells, a conservative Bonferroni adjustment was used, whereas in gated cells, the p-values were adjusted to control the false discovery rate according to Benjamini-Hochberg. A p-value of ≤0.05 was considered significant. Results: CR1 and CR2 ABC on bulk B cells and on IgD +CD27-, IgD +CD27+, and IgD-/CD27 +gated B cells was negatively associated with lupus disease activity, whereas there was no association between CR1 and CR2 ABC on IgD-/CD27- B cells or frequency of any of these gated populations and disease activity (table 1 and data not shown). Conclusions: Both CR1 and CR2 levels are negatively associated with lupus disease activity in defined B cell subsets. Although this study does not prove causality, these data suggest that altered levels of these receptors on specific B cell subsets may predict disease flare or be associated with disease remission. Acknowledgements: This work was supported by R01AI070304, K24AI078004, and the Lupus Research Institute.